2011
DOI: 10.1016/j.coi.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The narrowing of the CD8 T cell repertoire in old age

Abstract: Summary Immune function declines progressively with age, resulting in increased susceptibility of the elderly to infection and impaired responses to vaccines. A diverse repertoire of T cells is essential for a vigorous immune response, and an important manifestation of immune aging is the progressive loss of repertoire diversity, predominantly among CD8 T cells in both mice and humans. Importantly, perturbations in the peripheral T cell repertoire, including reduction of the CD4:CD8 ratio and cytomegalovirus-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
1
73
1
Order By: Relevance
“…Aging is associated with altered immune responses to vaccination, infection, cancer, and dysregulation of inflammatory responses [9,10]. In addition to a decrease in naïve T-cell numbers due to thymus involution [11,12], functional impairment of T cells is a major component of the defective immune response in the elderly [13]. In particular, an early and transient IL-2 secretion defect in aged T cells leads to impaired proliferation and differentiation in fully functional Th1 and Th2 cells [14,15].…”
Section: Extrathymically Induced Foxp3mentioning
confidence: 99%
“…Aging is associated with altered immune responses to vaccination, infection, cancer, and dysregulation of inflammatory responses [9,10]. In addition to a decrease in naïve T-cell numbers due to thymus involution [11,12], functional impairment of T cells is a major component of the defective immune response in the elderly [13]. In particular, an early and transient IL-2 secretion defect in aged T cells leads to impaired proliferation and differentiation in fully functional Th1 and Th2 cells [14,15].…”
Section: Extrathymically Induced Foxp3mentioning
confidence: 99%
“…From animal experiments, it has been suggested that the diversity of the immune receptor repertoire critically governs primary immune responses against pathogens (11)(12)(13).…”
Section: Reduced Initial Naive Cd8mentioning
confidence: 99%
“…Fifty milliliters of venous blood was drawn immediately before vaccination (day 0) and at eight further time points [days 2 (only donors 15-27), 4, 7, 10, 14, 17, 21, and 28] after vaccination into sodium heparin, serum gel, or EDTA tubes (BD Biosciences, Plymouth, U.K.). The study was run in three individual rounds [round I (donors 1-6), round II (donors [8][9][10][11][12][13][14], and round III (donors 15-27, additional study day 2)] and the obtained data sets were cross-checked for variability between runs before being merged for analysis. To study long-term YF-specific memory formation and stability, we collected in each case 50 ml venous blood from 19 of 23 vaccinees reinvited 33 (donors 1-6), 30 (donors [8][9][10][11][12][13][14], or 20 (donors 15-27) months after vaccination.…”
Section: Vaccination and Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the diversity of the repertoire (Ahmed, Lanzer et al 2009), decreases the potential to drive an immune response and affects the CD4/CD8 ratio (LeMaoult, Messaoudi et al 2000;Messaoudi, Lemaoult et al 2004 ;Clambey, van Dyk et al 2005;Goronzy and Weyand 2005;Pawelec, Akbar et al 2005;Clambey, Kappler et al 2007) reviewed in (Blackman and Woodland 2011). With age CD4 T cells have increased longevity (Tsukamoto, Clise-Dwyer et al 2009) while under normal homeostatic conditions recent thymic migrant have to compete with already established mature naïve T cells (Houston, Higdon et al 2011).…”
mentioning
confidence: 99%